Genetic characterization of the Turkish gray hamster (Cricetulus migratorius) based on mitochondrial cytochrome b and 12S rRNA sequences. (18th August 2018) - İbiş, Osman; Kılıç, Metin; Özcan, Servet; Tez, Coşkun
Abstract: Although genetic diversity and phylogenetic status of the gray hamster ( Cricetulus migratorius ) have been investigated from different regions in previous studies, genetic data on this species from Turkey are still lacking, since previous data have been based on a limited number of gray hamsters sampled across the Anatolian part of Turkey. The aim of this study was to determine the genetic diversity of the Anatolian population and to reveal the phylogenetic relationships among the Anatolian population and conspecific populations of the gray hamster. The complete and partial fragments of mitochondrial Cyt b and 12S rRNA from the 20 Turkish samples were amplified and sequenced. Ten 12S rRNA (901 bp) and 15 Cyt b (1140 bp) haplotypes found in this work were not previously reported. Based on Bayesian, Maximum Likelihood, Neighbour-Joining and Median-Joining network analyses by using mitochondrial data under the name Cricetulus, the results of phylogenetic and network analyses indicated that there was a deep separation among the distinct lineages within the genus Cricetulus . When considering the position of the Turkish haplotypes in median joining network, the Anatolian part of Turkey may have hosted a source population of the gray hamster for expansion to adjacent regions in the past period. Additionally, the Anatolian population of gray hamster had relatively high haplotype diversity and the present study propounded the importance of data obtained from the Anatolian population of gray hamster to reveal the phylogenetic relationships among conspecific populations of the gray hamster.